Thermal properties and non-bonded interactions in human PMP2 variants: A molecular dynamics study - Aryal, Prabin; Powrel, Jhulan (BIBECHANA, 2025)
Charcot-Marie-Tooth disease, a genetic disorder linked to mutations in the peripheral myelin protein 2, currently lacks an effective cure. In this study, we have used molecular dynamics simulations, focusing on non-bonded interactions and thermal properties, to explore the effects of M114T mutation on PMP2 at the temperatures of 305K, 310K and 315K. Our findings indicate that the mutation slightly destabilizes PMP2, reducing its structural integrity by decreasing hydrogen bonds and altering few salt bridges, although the differences are minimal. Additionally, the mutant exhibits slightly increased thermal diffusivity. A non-linear change in Cv with temperature was also observed in both protein systems. This work further extends to verify the Maxwell-Boltzmann distribution law and demonstrate the Gaus- sian nature of the temperature fluctuations in the protein systems.